2002
DOI: 10.2172/15003681
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity and Shear Strength of K Basin Sludge

Abstract: To provide input for the design and modeling of sludge storage systems, Pacific Northwest National Laboratory, under contract to the Fluor Hanford Spent Nuclear Fuel (SNF) Project, performed thermal conductivity and shear strength measurements on representative sludge samples from the Hanford K East (KE) Basin: floor sludge, canister sludge, and a composite of floor and canister sludge plus spent fuel fragments. This work was performed in the High Level Radiochemistry Facility (hot cells) located in the Radioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The original T-204 core sample without any dilution was 31.5 wt% total solids and had a shear strength of 1520 Pa . Poloski et al (2003) reported the second measurement on a pretreated AZ-101 waste sample. The initial sample had 10.3 wt% UDS, and the settled layer had 22 wt% UDS.…”
Section: 3mentioning
confidence: 99%
“…The original T-204 core sample without any dilution was 31.5 wt% total solids and had a shear strength of 1520 Pa . Poloski et al (2003) reported the second measurement on a pretreated AZ-101 waste sample. The initial sample had 10.3 wt% UDS, and the settled layer had 22 wt% UDS.…”
Section: 3mentioning
confidence: 99%
“…Most measurements given in Poloski et al (2002) were obtained from sludge samples that been settled/gelled for several days to several weeks. For some K-Basin sludge samples that had settled/gelled for 20 to 30 days, the shear strength ranges from 1 to 8200 Pa (Poloski et al 2002, Plys and Schmidt 2009, Schmidt 2010. The shear strength of the 96-13 sample of K East Basin sludge was estimated to be 15 to 65 kPa after 28 months stored under hot cell storage conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The shear strength of the sludge is one of the key sludge properties to determine whether water jets would mobilize the stored sludge in the STSCs (Onishi et al 2010). The shear strength is affected by sample history among other factors, and most of the measurements given in Poloski et al (2002) were obtained from sludge samples that had been settled/gelled for several days to several weeks. These include the shear strength range of 1 to 8200 Pa reported for K-Basin sludge samples (predominantly collected from the KE floor, KE pits, and KE canisters) from 1995-2002(Poloski et al 2002, Plys and Schmidt 2009, Schmidt 2010.…”
Section: 3mentioning
confidence: 99%
“…Most prior sludge strength measurements were obtained for sludge that had been quiescent for several days to several weeks (Poloski et al 2002). Shear strengths ranging from 1 to 8200 Pascals (Pa) have been reported for K Basin sludge samples predominantly collected from the KE floor, KE pits, and KE canisters from 1995 to 2002 (Poloski et al 2002;Schmidt and Sexton 2009;Schmidt 2010). These measurements were mostly conducted for samples that had settled for up to 20 to 30 days.…”
Section: Prior Sludge Strength Observationsmentioning
confidence: 99%